2020
DOI: 10.1111/cts.12904
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Prescribed Ibuprofen and Severe COVID‐19 Infection: A Nationwide Register‐Based Cohort Study

Abstract: Recommendations regarding ibuprofen use in relation to coronavirus disease 2019 (COVID-19) have been conflicting. We examined the risk of severe COVID-19 between ibuprofen-prescribed and non-ibuprofen patients with COVID-19 in a nationwide register-based study of patients with COVID-19 in Denmark between the end of February 2020 and May 16, 2020. Patients with heart failure (n = 208), < 30 years (n = 575), and prescribed other nonsteroidal anti-inflammatory drugs (n = 57) were excluded. Patients with ibuprofen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…[47][48][49] More recent studies, however, found no significant evidence to suggest that ibuprofen is associated with severe COVID-19 outcomes. 50,51 Further, an observational study using EHR data from 6 hospitals indicated that exposure to ibuprofen is associated with a lower risk of hospitalization due to COVID-19 (OR, 0.73; 95% CI, 0.64-0.84). 52 A retrospective study using EHR data showed a decreased fatality rate for women 50+ years old receiving estradiol therapy (OR, 0.33; 95% CI, 0.18-0.62).…”
Section: Discussionmentioning
confidence: 99%
“…[47][48][49] More recent studies, however, found no significant evidence to suggest that ibuprofen is associated with severe COVID-19 outcomes. 50,51 Further, an observational study using EHR data from 6 hospitals indicated that exposure to ibuprofen is associated with a lower risk of hospitalization due to COVID-19 (OR, 0.73; 95% CI, 0.64-0.84). 52 A retrospective study using EHR data showed a decreased fatality rate for women 50+ years old receiving estradiol therapy (OR, 0.33; 95% CI, 0.18-0.62).…”
Section: Discussionmentioning
confidence: 99%
“…These preliminary findings are consistent with the findings of no increased risk of severe illness in the available studies to date. For instance, Kragholm et al ( 2020 ) reported in their retrospective database review that patients with pre-diagnosis use of NSAIDs had no increased risk for a composite outcome of severe disease, intensive care unit admission, or death, relative to non-use of NSAIDs (risk ratio = 0.96; 95% confidence interval 0.72–1.23).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…As a result, they have no information about ibuprofen in asymptomatic carriers, and whether antipyretics can influence their clinical course 16 . Third, the main analysis of these studies compared NSAID users with non-NSAID users, but confounding indicators may have influenced the results 14 , whereas ibuprofen users were defined based on prescription fills and information on whether or how many ibuprofen pills the patients actually took is not available 15 . Ibuprofen also can be purchased as an over-the-counter drug, they cannot exclude potential misclassification of ibuprofen exposure, as patients in the non-ibuprofen group may have used over-the-counter ibuprofen 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Neither the acute nor the chronic use of NSAIDs resulted in increased mortality or severe COVID-19 14 . Also, Kragholm and colleagues reported the data of a retrospective, Danish-based cohort study, including 4002 adults with COVID-19 of whom 264 (6.6%) were treated with ibuprofen 15 . Again, no significant association between ibuprofen and severe COVID-19 was found.…”
Section: Introductionmentioning
confidence: 99%